2003
DOI: 10.1038/sj.ejcn.1601580
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical characteristics of patients with home enteral nutrition in an area of Spain

Abstract: Objective: The widespread use of long-term enteral nutrition and the substantive costs dictate a need to study outcome, clinical and epidemiological characteristics of these patients. The aim of our study was to analyze incidence, clinical and biochemical characteristics of a cohort of patients on home enteral nutrition (HEN). Design: Prospective observational study. Setting: Tertiary care. Subjects: Between January 1999 and December 2001, all adult patients living in Valladolid West area who were discharged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
0
5
0
6
Order By: Relevance
“…Home enteral nutrition is defined as the provision of enteral diets as the main source of daily intake at home. During recent years, the use of HEN has increased enormously, both because of its reliability and because of the need for National Health Services to discharge chronically ill patients (De Luis et al, 2006). This increase has triggered the development of specific legislation, guidelines and national registries in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…Home enteral nutrition is defined as the provision of enteral diets as the main source of daily intake at home. During recent years, the use of HEN has increased enormously, both because of its reliability and because of the need for National Health Services to discharge chronically ill patients (De Luis et al, 2006). This increase has triggered the development of specific legislation, guidelines and national registries in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…Improving or maintaining nutrition status is the main aim of ETF 2 . Over the past 2 decades, numerous studies on home enteral nutrition (EN) demonstrated that it is a valid and safe technique for nutrition support 3 , 4 . Long‐term ETF can be a source of discomfort and esophagitis and predisposes to nasal and maxillary sinus inflammation 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these patients who were considered to be on HEN, oral nutrition was the preferential route in 50.8%, followed by nasoenteral tube (30%), and in 17.4% ostomy tubes were placed. A prospective observational study was also performed in the Valladolid area in Spain between January 1999 and December 2001 showing that HEN was administered orally to 79% of the patients [10].…”
Section: Definitionmentioning
confidence: 99%